2003
DOI: 10.2320/matertrans.44.2384
|View full text |Cite
|
Sign up to set email alerts
|

Composition/Phase Structure and Properties of Titanium-Niobium Alloys

Abstract: This study attempts to develop Ti-Nb alloys with elastic moduli that approach that of human bone. The experimental results reveal that the microstructure of a Ti-Nb alloy that contains 14 mass% Nb consists of and phases, with phase being the dominant one. The proportion of the phase decreases gradually as the Nb content increases, and the microstructure becomes completely the phase when the Nb content exceeds 34 mass%. Moreover, the ! phase can be detected using XRD and TEM in alloys with a Nb content from 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
0
17

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(154 citation statements)
references
References 21 publications
12
125
0
17
Order By: Relevance
“…It is worth here that the reason for the variations of the elastic modulus due to different processing need to be explored. The presence of other phases, such as αc, αcc and Z, is known to have a strong influence on the modulus [11,15,60]. Thus, the analysis of the microstructural constituents may provide clues as to the behavior of the alloys at different processing conditions.…”
Section: Experimental Validationmentioning
confidence: 99%
“…It is worth here that the reason for the variations of the elastic modulus due to different processing need to be explored. The presence of other phases, such as αc, αcc and Z, is known to have a strong influence on the modulus [11,15,60]. Thus, the analysis of the microstructural constituents may provide clues as to the behavior of the alloys at different processing conditions.…”
Section: Experimental Validationmentioning
confidence: 99%
“…It can be observed that the yield strength as well as the compression strength at 35% increases with increasing energy input and the density of the samples. A highest compressive strength at 35% strain of ~723 MPa is observed for the sample with the highest energy input of 257 J/mm 3 However, the compressive modulus was observed to be ~30-50 GPa higher than the Ti-45Nb alloy prepared by other conventional routes [6,28,29], which might be attributed to the fine microstructure. Thanks to the advantage of such additive manufacturing processes, modification in the modulus can be incorporated in the form of introducing structures in the samples instead of the bulk samples.…”
Section: Compression Testsmentioning
confidence: 74%
“…16,18) Some researchers reported that higher amounts of protein present on the implant surface can provide better tissue healing and hence better osseointegration. 18) The present authors have developed certain Ti-Nb-based alloys, 2) e.g., Ti-40Nb-1Hf, which has been shown to exhibit excellent properties combination of relatively high strength and low modulus (UTS: 893 MPa, 0.2% Proof stress: 841 MPa and E: 65 GPa), and can be considered quite suitable for implant applications. Therefore, this study chose Ti-40Nb-1Hf alloy as the subject alloy, and was conducted with the following two objectives: Firstly, to investigate the effect of surface treatment or modification by employing glow discharge plasma treatment (Ar-and O 2 -plasma) on the surface characteristics of Ti-40Nb-1Hf alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Ti-Nb-based alloy is one of the commonly applied implant biomaterials. [1][2][3] Due to the fact that the implant surface will contact the host tissue directly, the surface characteristic will play an important role in determining implants' biocompatibility. However, the surface characteristics of biomaterials may change or degrade with time, mainly due to contamination.…”
Section: Introductionmentioning
confidence: 99%